Pola Komunikasi Suku Samin di Kabupaten Blora terkait Ajaran yang Dianutnya - Octaviani, Emillia Vinna (Jurnal The Messenger, 2015)
The aim of this study determines the communication pattern samin tribal culture to the community in Blora related teachings espoused, and know the pattern of tribal cultural communication to the outside community cumin cumin in Blora related teachings espoused. The theoretical basis of communication used the symbolic interactionism. This theory explains humans interact and exchange of meaning, create, send, receive symbol agreed. The method used is the in-depth interviews and observation. Researchers chose purposive sampling as a technique of sampling . The case study research in Samin Tribe and the village of Sambong Klopoduwur District of Banjarejo.